How Ibn Khaldun's Concept of Demand Related to Indonesia’s Economic Growth? - Larasati, Dorothea; Setyanti, Axellina Muara (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Ibn Khaldun stated that the demand for a good is influenced by the factors of price, income, population, community habits, and the level of social prosperity. If the quantity of goods is limited, prices will increase and may cause inflation. This phenomenon can be observed in the case of scarcity of goods in Indonesia, such as LPG and cooking oil, which causes price spikes and reduces people's purchasing power. In addition, consumptive consumption patterns contribute to price instability and inflationary pressures. This study uses a qualitative research method with a literature study approach to analyze the relevance of Ibn Khaldun's theory to Indonesian economic phenomena. The results show that this theo-ry is still relevant in understanding the dynamics of demand and modern economic growth. The decline in demand in the industrial sector, as seen in the deindustrialization process in Indonesia, is also evidence of the importance of the balance between supply and demand. Therefore, effective economic policies are needed to control inflation and price stability. In addition, students as agents of change are expected to understand classical and modern economic concepts and contribute to entrepreneurship and wise consumption education.